Prevalence of methicillin-resistant Staphylococcus aureus (MRSA) among healthcare workers in Yafran general hospital - Khaled Abdusalam Bashir; Alaa Muhammed Argoup; Heba Ahmeda Ali; Heba Khalid Jama; Shahed Muhammed Jama; Mawada Ebrahim Zerbiga (African Journal of Advanced Pure and Applied Sciences, 2024)
Nasal carriage of MRSA among hospital personnel is a big problem in hospital environment. Accordingly, the main objective of current study was to determine the prevalence of MRSA among Health Care Workers (HCWs) in Yafran hospital. 108 HCWs samples of nasal swabs were collected, and cultured on Mannitol Salt Agar. The isolates were identified as S. aureus based on morphology. Besides, confirmatory tests were performed, including coagulase and catalase test. Finally, cefoxitin disc resistance was used to identify the MRSA strain. Antibiotic susceptibility testing of MRSA was performed according to the guidelines of the Clinical and Laboratory Standards Institute. The results showed that, out of the 108 HCWs, 37 (34%) carried MRSA. MRSA carriage rate was highest among Administration Department workers 30 % compared to other professions, followed by Emergency Department workers 21% , Obstetrics and Gynecology workers 19 %, Radiology, Laboratory and Internal Medicine Department workers was 8% ,5% and 5% respectively. Tetracycline showed the highest rate of resistance among MRSA isolates 27%, followed by Vancomycin 22%. While the Ciprofloxacin showed less resistance 11%. In conclusions, the high rate of nasal MRSA carriage among healthcare workers found in this study is alarming and highlights the need for adjusted infection control measures to prevent MRSA transmission from HCWs to the vulnerable patient.